Destruction of nitrocarbonized steel - A. M. Apasov; A. A. Apasov; E. V. Kozlov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2009)
The it authors have studied the structure of steel subjected to carbonitriding and subsequent heat treatment to determine the reasons of its destruction. The mechanism of hear cracks initiation was defined and their evolution trajectories were determined.